The Regulation of Legal Responsibility: Illegal Logging Perpetrators in Indonesia and Nigeria - Akhmaddhian, Suwari; Okolie, Ugo Chuks; Hidayat, Sarip; Andriyani, Yani; Tiaranita, Intan (Unifikasi : Jurnal Ilmu Hukum, 2023)
The study aims to analyze the offenders of illegal logging in Indonesia and Nigeria from their legal liability regulations. The study employed a socio-legal approach involving literary analyses of legal materials used—the statutory regulations, scientific journals, and other pertinent documents. The results show that legal responsibility for illegal logging perpetrators in Indonesia is under the Law on Forestry, the Law on Prevention and Eradication of Forest Destruction, and the Law on Job Creation. In Nigeria, it is governed by several states, such as the Edo State Forestry (Amendment) Law 2002, the Cross River State Forestry Commission Law 2010, and the Taraba State Forestry Law 2010. Finally, the legal responsibility for illegal logging has been established in both countries. Accordingly, the Indonesian government is suggested to disseminate the latest laws and regulations so that the public and corporations are aware of them. Meanwhile, the Nigerian government is expected to immediately issue nationwide legislation on illegal logging so that law enforcement is not relied solely on the requirements of each state.